The role of the National Museum in the development of cultural tourism in Kazakhstan (Journal of history, 2020)
Cultural tourism is the most popular and mass type of tourism, the special place in this direction is occupied by museums. In the whole world cultural tourism a long ago was distinguished in separate direction and with every year gets all greater development in Kazakhstan. The article is sanctified to the range of problems of cultural tourism, about the features of development of this direction in Kazakhstan. Development of cultural tourism is in Kazakhstan, it is necessary to consider on the example of the National museum of RК, so the national museum of RК conforms to the basic requirements of tourist resources. The author of the article was given detailed analysis of historical – cultural and tourist potential of the National museum of RК. Descriptions of some exhibits that are the «visiting-card» of museum were also given. In the conclusion of the article showed the role of the National museum of Republic of Kazakhstan in development of cultural tourism in Kazakhstan. Key words: Kazakhstan, culture, tourizm, natoinal museum of rk.